The specificity of teacher reflectivity in early education teachers – a study report - Joanna Szymczak; Adam Mroczkowski (Problemy Wczesnej Edukacji)
This article presents selected results of a preliminary research of teacher reflectivity. The empirical material was collected through the original Early Education Teacher Reflectivity Questionnaire on (pre)School Daily Life. It was answered by early education teachers and graduate students of early childhood pedagogy. The article also describes the understanding of reflectivity adopted here, along with its importance for building awareness of what it means to be a teacher with regard to reflection. Furthermore, careful consideration was given to the presented results followed by reflections on the results of the study. The analysis indicated that teachers in the study group did have a problem with identifying criteria for selecting situations to which they assigned a critical dimension. They seemed to lack insight into themselves. In their analyses, they evaluated individual aspects of a given event, but did not pose questions that might motivate in-depth reflection. Moreover, they equated anticipating the position of other persons about a given incident with experiencing a variety of perspectives. They avoided involving other people in the process of analyzing a situation, thus depriving themselves of an opportunity to develop transformative learning abilities. At their current stage of professional education, they showed a need for support, which may be aided by the assumptions of the humanistic concept of teacher education and the emancipatory rationality.